Perbedaan Kedalaman Bilik Mata Depan Sebelum dan Sesudah Operasi Katarak Fakoemulsifikasi Disertai Tanam Lensa - Shelly Nabila; Sony Santoso; Nina Handayani (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Cataract remains the leading cause of visual impairment and blindness worldwide. Cataract surgery utilising phacoemulsification technique with intraocular lens implantation may induce alterations in anterior chamber depth. This study aimed to compare anterior chamber depth before and after phacoemulsification cataract surgery with intraocular lens implantation. The research methodology employed a retrospective analytical design based on medical records of cataract during the period January–December 2019. Data collected included age, sex, operative eye side, and pre- and postoperative anterior chamber depth, which were subsequently analysed using SPSS software. The sampling technique utilised was consecutive sampling, yielding 125 subjects who fulfilled the inclusion criteria. Results demonstrated that the majority of patients were aged >60 years (64.8%), with females comprising the largest group (51.2%), and the left eye representing the most frequent operative side (51.2%). Paired sample t-test analysis revealed a significant difference in anterior chamber depth before and after surgery (p=0.000). Pearson correlation analysis also demonstrated a significant negative relationship between preoperative anterior chamber depth and postoperative changes (p<0.05). The conclusion of this study is that there was a significant increase in anterior chamber depth following phacoemulsification cataract surgery with intraocular lens implantation, as well as a significant relationship between preoperative anterior chamber depth and postoperative changes.